New record of Epermenia (Calotripis) sinjovi Gaedike (Lepidoptera: Epermeniidae) in China: DNA barcode, adult, immature stages, host plant and biology - Wang, Yehao; Teng, Kaijian; Liu, Tengteng (Zootaxa, 2021)
Epermenia (Calotripis) sinjovi Gaedike, 1993, feeding on Angelica pubescens Maxim. and A. ursina Maxim., was previously recorded in Russia (Far East, Southern Siberia and Transbaikalia), Kunashir Island and Japan. This species is for the first time reported in China by rearing from a new host plant A. polymorpha Maxim. The larva and pupa are illustrated and described for the first time. Available biological information associated with the new host plant is also reported. Reference DNA barcodes are provided for E. (C.) sinjovi, which confirms that forewing distinct colors and morphological differences found in venation and genitalia among individuals are intraspecific variations. The adult morphological variations within population are analyzed and discussed.